2022
DOI: 10.1155/2022/3787162
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Potential Poly (ADP-Ribose) Polymerase-1 Inhibitors Derived from Rauwolfia serpentina: Possible Implication in Cancer Therapy

Abstract: Poly (ADP-ribose) polymerase-1 (PARP-1) has been recognized as a prospective target for the development of novel cancer therapeutics. Several PARP-1 inhibitors are currently being considered for anticancer drug development and clinical investigation. Lately, natural compounds seem to be excellent alternative drug candidates for cancer treatment. Rauwolfia serpentina is a medicinal plant traditionally used in Indian subcontinents to treat various diseases. This study has been designed to identify the bioactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…The masking of positive charge on lysine and arginine by nanoparticles, considered as inhibitory action of nanoparticles 9 . Since over the last few years, researchers showing their interest in searching better disease preventing agents from plant derived phenolic and other bioactive compound to plant‐based bio‐synthesized nanoparticles 54‐58 . To confirm the antiglycating property of TNP, together with inhibitory protein modification action, the reduction in the ketoamine, carbolnyl content and AGEs formation observed in our study confirmed the efficacy of the antiglycation effect of plant based TNP.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The masking of positive charge on lysine and arginine by nanoparticles, considered as inhibitory action of nanoparticles 9 . Since over the last few years, researchers showing their interest in searching better disease preventing agents from plant derived phenolic and other bioactive compound to plant‐based bio‐synthesized nanoparticles 54‐58 . To confirm the antiglycating property of TNP, together with inhibitory protein modification action, the reduction in the ketoamine, carbolnyl content and AGEs formation observed in our study confirmed the efficacy of the antiglycation effect of plant based TNP.…”
Section: Resultssupporting
confidence: 81%
“…9 Since over the last few years, researchers showing their interest in searching better disease preventing agents from plant derived phenolic and other bioactive compound to plant-based biosynthesized nanoparticles. [54][55][56][57][58] To confirm the antiglycating property of TNP, together with inhibitory protein modification action, the reduction in the ketoamine, carbolnyl content and AGEs formation observed in our study confirmed the efficacy of the antiglycation effect of plant based TNP. Although, TNP mechanism of action is not very clear and understood; hence, its inhibitory mechanism against the glycation is a matter of further investigation.…”
Section: Ans-hydrophobicity Change Detection By Fluorescence Spectrasupporting
confidence: 78%
“…Agents that prevent cancer initiation are customarily termed ‘blocking agents’. They work by reducing the interaction between chemical carcinogens and DNA, thus reducing the level of damage [ 121 ]. Once beginning has arisen, chemopreventive compounds might impact on the promotion and progression of initiated cells; such compounds are frequently termed ‘suppressing agents’ [ 110 ].…”
Section: Scientific Principles Related With Cancer Chemopreventionmentioning
confidence: 99%
“…These are a wide variety of bioactive non-nutrient compounds that occur naturally in fruits, vegetables, grains, and other plant foods with desirable health benefits beyond basic nutrition and that could help prevent chronic diseases, including cancer. The last 3–4 decades have witnessed a plethora of scientific studies focused on phytochemicals, such as flavonoids, nonflavonoids, carotenoids, phenols, nitrogen-containing, and organosulfur compounds ( Figure 1 ), with diverse therapeutic potential against various cancer types [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Numerous epidemiological studies have also observed reduced cancer incidence with the use of phytochemicals [ 14 , 21 ].…”
Section: Introductionmentioning
confidence: 99%